STRUCTURE OF FUTURE READYNESS FOREIGN LANGUAGE TEACHERS TO PERSONAL ORIENTED LEARNING OF SENIOR STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the structure of the readiness of future teachers of the foreign language for personality-oriented teaching of high school students. The role of each component in the formation of this phenomenon is revealed.